Multisystem inflammatory syndrome in an adult after Covid-19 vaccination (MIS-V): a case report and review of published literature - Iftikhar, Namirah; Ashar Ekhlaq Ahmed; Muhammad Osama Rehman Khalid; Rameel Muhammad Aftab (Journal of the Pakistan Medical Association, 2024)
The novel coronavirus SARS-CoV-2 pandemic began in Wuhan (China) in December 2019. Due to the severity of the illness, extent and speed of its spread, vaccines were developed rapidly, and concerns have remained about their safety profile. Although the vaccines have proven to be safe and effective in most cases, as the number of people getting vaccinated for SARS-COV-2 increased, several adverse reactions following the administration of vaccine were reported, one of them being Multisystem Inflammatory Syndrome secondary to vaccination (MIS-V). Here, we report the case of a patient with MIS-V as well as a summary of all other published cases of this syndrome to-date. Keywords: Adverse events following immunisation, SARS-COV 2, Immunisation triggered inflammation, MIS-V, Immunisation related syndrome.